Peran Guru Dalam Mengimplementasi Model Cooperative Learning Tipe Berpasangam pada Pembelajaran Anak Usia Dini - Zega, Refni Fajar Wati; Zai, Suardin; Sunardi, Philipus (Indo Green Journal, 2024)
Early childhood education is the most important and most important thing. However, teaching early childhood requires various good and correct teaching models because children at this age easily get bored with learning. This kind of learning which is a problem for the teaching and learning process of early childhood is monotonous learning which occurs when the teacher only explains and takes notes and requires young children to actively take notes and just listen. Therefore, the author suggests a method that is good and suitable for use in teaching early childhood, namely the cooperative learning model in pairs. This learning model aims to make young children active positively, such as actively asking questions, actively discussing, and having the desire to learn because they have study friends. In accordance with the explanation above, the aim of this study is to explain how to implement the cooperative learning model in early childhood learning. The research method used is a descriptive qualitative approach with a literature review method. Data collection techniques through books and journal articles related to problems raised by the author as references. So the results obtained from the cooperative learning model in pairs can be implemented easily for young children and at the same time also improve children's cognitive abilities and increase children's ability to adapt to their friends.